2001
DOI: 10.1007/s004450100164
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular komatiites, 3.5-Ga Komati Formation, Barberton Greenstone Belt, South Africa: inflation of submarine lavas and origin of spinifex zones

Abstract: Komatiites of the 3.5-Ga Komati Formation are ultramafic lavas (>23% MgO) erupted in a submarine, lava plain environment. Newly discovered vesicular komatiites have vesicular upper crusts disrupted by synvolcanic structures that are similar to inflation-related structures of modern lava flows. Detailed outcrop maps reveal flows with upper vesicular zones, 2-15 m thick, which were (1) rotated by differential inflation, (2) intruded by dikes from the interior of the flow, (3) extended, forming a flooded graben, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Vesicles are generally sparse in komatiite lavas (Arndt et al 2004) when compared to high vesicle density in their basaltic counterparts, possibly related to the low volatile content or their accumulation and preservation in high-temperature, low-viscosity lavas. The low percentage (~1%) of vesicular komatiite in most J.C. Pura sections is similar to that reported by Dann (2001) for komatiite sequences from the Barberton Greenstone Belt. Based on the disposition of vesicular horizons, it is envisaged that at least two distinct stages of vesiculation were associated with the J.C. Pura komatiite flows.…”
Section: Physical Volcanology and Emplacement Conditionssupporting
confidence: 86%
“…Vesicles are generally sparse in komatiite lavas (Arndt et al 2004) when compared to high vesicle density in their basaltic counterparts, possibly related to the low volatile content or their accumulation and preservation in high-temperature, low-viscosity lavas. The low percentage (~1%) of vesicular komatiite in most J.C. Pura sections is similar to that reported by Dann (2001) for komatiite sequences from the Barberton Greenstone Belt. Based on the disposition of vesicular horizons, it is envisaged that at least two distinct stages of vesiculation were associated with the J.C. Pura komatiite flows.…”
Section: Physical Volcanology and Emplacement Conditionssupporting
confidence: 86%
“…These samples were from the tumulus, a thick, differentiated, entirely serpentinized komatiite flow described by Dann (2001). Three of these latter ten samples are classified as hyaloclastite, one as olivine orthocumulate, one as olivine adcumulate, one as harrisite, two as spinifex textured komatiite, one as pyroxenite, and one as gabbro (Arndt et al, unpublished results).…”
Section: Komatiites and Tholeiitesmentioning
confidence: 99%
“…Grove and coworkers [ Grove et al , 1997, 1999; Parman et al , 1997] recently suggested that komatiites from the type section in the Barberton Greenstone Belt in South Africa [ Viljoen and Viljoen , 1969] were emplaced not as lava flows but as a series of high‐level intrusions. The situation has since become clearer, however, with the publication by Dann [2000, 2001] of detailed maps that show conclusively that these units are extrusive. Their morphological features and textures are very like those of lava flows in other regions and there is no reason to believe that they formed in a different manner.…”
Section: Komatiitesmentioning
confidence: 99%